Curcumin as a novel therapeutic candidate for cancer: can this natural compound revolutionize cancer treatment? - Ameer, Shadiya Fawzul; Mohamed, Muna Yusuf; Elzubair, Qubaa Ahmed; Sharif, Elham Abdullatif M.; Ibrahim, Wisam Nabeel (Frontiers in Oncology, 2024)
Cancer remains one of the leading causes of death worldwide. Despite advances in medical treatments, current therapeutic strategies, including radiotherapy, chemotherapy, targeted therapy, and surgical resection, have not significantly reduced the global incidence and mortality rates of cancer. Oncologists face considerable challenges in devising effective treatment plans due to the adverse side effects associated with standard therapies. Therefore, there is an urgent need for more effective and well-tolerated cancer treatments. Curcumin, a naturally occurring compound, has garnered significant attention for its diverse biological properties. Both preclinical studies and clinical trials have highlighted curcumin’s potential in cancer treatment, demonstrating its ability to inhibit the proliferation of various cancer cell types through multiple cellular and molecular pathways. This paper examines the antineoplastic properties, and the therapeutic mechanisms including cell signalling pathways targeted by curcumin that are implicated in cancer development and explores the challenges in advancing curcumin as a viable anticancer therapy.